Failing to learn: The impact of failures during making activities. (December 2018) - Maltese, Adam V.; Simpson, Amber; Anderson, Alice
Highlights: Investigation of role of failure viewed by educators from making/makerspace contexts. More than 100 educators report views of failure that are slightly positive. Educators recommend helping students by teaching them how to troubleshoot themselves. Abstract: Making is a recent educational phenomenon that is increasingly occurring in schools and informal learning spaces around the world. In this paper we explore data from maker educators about their experiences with failure. We surveyed maker educators about how they view failure happening with youth in their formal and informal programs and how they respond. The results reveal some concrete strategies that seem to show promise for helping educators increase the likelihood that failure experiences for youth can lead to gains in learning and persistence.